Shear strengthening of concrete members with Textile Reinforced Mortar (TRM) - Tetta, Zoi (2017)
The issue of upgrading existing structures is of great importance due to their deterioration (ageing, environmental induced degradation, lack of maintenance, need to meet the current design requirements). Recently, an innovative structural material, the so-called Textile-Reinforced Mortar (TRM), was successfully developed for structural retrofitting of deficient masonry and concrete structures. TRM is an advanced sustainable material which offers well-established advantages (good behaviour at high temperature, compatibility to concrete or masonry substrates material high strength to weight ratio, corrosion resistance, ease and speed of application, minimal change of cross section dimensions) at a low-cost and over the last decade it has been reported in the literature that TRM is a very promising alternative to the FRP (Fibre Reinforced Polymers) retrofitting solution. This study evaluates the use of TRM jacketing for shear strengthening of Reinforced Concrete (RC) beams. First of all, the materials used for strengthening are described and the tensile and shear behaviour of textiles was characterised through tensile and picture-frame tests, repsectively. Moreover, the tensile properties of TRM composite material are experimentally obtained through bell-shaped TRM coupons. Shear strengthening of RC beams was extensively studied carrying out 55 medium-scale rectangular beams and 14 full-scale T-beam ends. The key investigated parameters on medium-scale rectangular beams comprise: (a) the strengthening system (TRM versus FRP), the (b) strengthening configuration, (c) the number of layers, (d) the external reinforcement ratio, (e) the textile material mesh characteristics, (f) the shear-span-to depth ratio and (g) the optimisation of the textile geometry. It was concluded that TRM was very effective on increasing the shear resistance of RC beams but its effectiveness was sensitive to parameters such as the strengthening configuration, the number of layers and the textile characteristics. Experimental work was also conducted on full-scale T-beams focused on the use of a novel end-anchorage system comprising textile-based anchors to delay or prevent the debonding of TRM jacket. In particular, the anchorage percentage of the U-jacket, the number of layers, the textile material, the textile geometry and the strengthening system (TRM versus FRP jackets) were the main investigated parameters. U-shaped TRM jackets significantly increased the shear capacity of full-scale T-beams, whereas the use of textile-based anchors improved dramatically the effectiveness of the TRM jackets. A simple design model was also proposed to calculate the contribution of anchored TRM jackets to the shear capacity of RC T-beams. The behaviour of TRM at high temperature used for shear strengthening of both medium-scale and full-scale beams was studied for the first time through demanding tests in which loading and high temperature were simultaneously applied. Based on the experimental results, TRM jacketing remained very effective at high temperature, whereas the effectiveness of side-bonding and U-wrapping FRP jacketing was reduced nearly to zero when subjected at temperatures above the glass transition temperature (Tg). A stress reduction factor for TRM and FRP systems was also introduced to take into account the decrease in the effectiveness of both TRM and FRP jacket due to explosion of specimens to high temperature. Finally, design models for the prediction of the contribution of the TRM jacket to the total shear resistance were proposed for each failure mode and verified with the available experimental data.